2002
DOI: 10.1203/00006450-200209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

COX-1 and COX-2 Contributions to Basal and IL-1β-Stimulated Prostanoid Synthesis in Human Neonatal Cerebral Microvascular Endothelial Cells

Abstract: Mechanisms of endothelium-dependent regulation of cerebral circulation in human neonates are poorly understood owing to the lack of experimental data. Prostanoids, the products of the cyclooxygenase (COX) pathway, appear to be important regulators of blood flow in neonates. COX activity in cultured endothelial cells from small (60 -300 m) and large (Ͼ300 m) microvessels from the autopsy specimens of neonatal human cerebral cortex and cerebellum (22-26 wk gestational age) was detected as production of vasodilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…We therefore performed Western blotting analyses to quantify the effect of DEX treatment on COX-1 or -2 protein abundance. As shown in fi gure 4 , we detected both COX-1 and -2 in our control samples, suggesting that both enzymes are constitutively expressed in near-term lamb carotids, similar to observations in human newborns and neonatal pigs [26,27] . However, we found that DEX treatment had no significant effects on COX-1 or -2 protein expression in our samples ( fi g. 4 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We therefore performed Western blotting analyses to quantify the effect of DEX treatment on COX-1 or -2 protein abundance. As shown in fi gure 4 , we detected both COX-1 and -2 in our control samples, suggesting that both enzymes are constitutively expressed in near-term lamb carotids, similar to observations in human newborns and neonatal pigs [26,27] . However, we found that DEX treatment had no significant effects on COX-1 or -2 protein expression in our samples ( fi g. 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…This data suggests that DEX may alter the balance between the PLC and phospholipase A 2 pathway, stimulating an increase in vasodilator prostanoids while inhibiting the signal transduction pathway, leading to contraction. Additional mechanisms by which DEX can result in vasodilation are the possible effects of DEX on COX isoform and subcellular localization [34] , post-translational regulation [25], and other pathways downstream from COX, such as the conversion of arachidonate to prostaglandin E 2 [27] and the activities of other arachidonic metabolites such as epoxyeicosatrienoic [35] or leukotrienes [36] .…”
Section: Discussionmentioning
confidence: 99%
“…The assessed COX-dependent responses mainly require COXproducts from endothelial cells, since selective endothelial injury diminishes the responsiveness to these stimuli (14,15). Indeed, freshly isolated or cultured endothelial cells from piglet brains or autopsy specimens of neonatal human cerebral cortex have also been found to produce prostanoids mainly via the activity of COX-2 (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important observation because it suggests that macrophage penetration into white matter occurs at lower doses of LPS required to provoke the response elsewhere in the brain. Macrophages respond to a wide range of microbial products such as LPS using a toll-like receptor on their surface (33), initiating host-defense mechanisms by release of cytokines, particularly IL-1 and TNF-␣. Macrophage infiltration is a well-defined response to systemic and CNS infections in the adult brain (26,42), and the presence of activated monocytes of peripheral and in situ origin (i.e.…”
Section: Fetal Blood-brain Barrier and Endotoxinmentioning
confidence: 99%